Diabetes, but not pre-diabetes, is associated with shorter time to second-line therapy and worse outcomes in patients with multiple myeloma. Issue 11 (19th September 2021) - Avivi, Irit; Yekutiel, Naama; Cohen, Inbar; Cohen, Yael C.; Chodick, Gabriel; Weil, Clara
Abstract: About 20% of MM patients have T2DM. We assessed the impact of T2DM/pre-T2DM on MM progression and OS. We collected retrospective data of newly diagnosed MM patients in Maccabi health services, Israel, between 2012 and 2016. The study included 503 MM patients, median age 67.2 years (IQR: 33.5–91.2). Median follow-up was 32 months (IQR 19.4–47). T2DM and pre-T2DM were recorded in 24.1% and 51% patients, respectively. Median TT2T and OS in the cohort were 17.5 months (95% confidence interval (CI) 15–20) and unreached, respectively. T2DM patients had shorter TT2T (HR = 1.31, 95%CI 1.0–1.72, p =.047), particularly transplanted patients; 20.2 vs. 40 months (HR = 2.09, 95%CI 1.18–3.71, p =.012). In a multivariable model, T2DM had a borderline significant risk of all-cause mortality, adjusted HR 1.38 ( p =.09). Pre-diabetes had no impact on TT2T or OS. T2DM predicted a shorter TT2T, particularly in transplanted patients, and tended to be associated with shorter survival.